Water quality of a southwest Iberian coastal lagoon: Spatial and temporal variability. (1st August 2022) - Rosa, Alexandra; Cravo, Alexandra; Jacob, José; Correia, Cátia
Abstract: The present work aims to characterize Ria Formosa water quality considering its spatial, and temporal variability at two scales: short-term (among seasons) and long-term to evaluate its evolution over the past 40 years, by comparing six historical datasets with data obtained in this study. To attain these goals, four field surveys under different seasons and/or weather conditions were conducted between 2017 and 2019 at seven sites along the Ria Formosa, covering the water bodies specified for this system. In situ measurements (temperature, salinity, pH and dissolved oxygen) and water sampling for determination of nutrients, chlorophyll a and suspended solids were taken every 2 h at each site, during complete semidiurnal tidal cycles. Moreover, these data were complemented with in situ data acquired at a high frequency (every 15 min) by a real time observational station deployed at an inner area, close to a main channel, where the anthropogenic pressure is more intense. Data analysis clearly depict a spatial variability pattern along the Ria Formosa, as well as a temporal heterogeneity, influenced by the contribution of precipitation, sediments, wind and water exchanges with the adjacent ocean. Between sampling sites, the lowest variability of water quality parameters occurred at the boundary coastal station, at the main inlet, in permanent connection with the ocean, while the maximum variability was found at both the lagoon edges, mainly due to the shallowness of the water column. Temporally, the highest concentrations of nutrients were obtained during the Wet/rainy conditions survey, under the influence of runoff. The lowest concentrations of nutrients were attained during the Summer, except for phosphate, due to consumption by phytoplankton. Although the sampling frequency along time has been limited, Ria Formosa water quality data from the last 40 years shows a decreasing trend in nutrients concentration and a marginal increase of dissolved oxygen, suggesting a water quality improvement over time, in contrast with other coastal lagoons that are showing a water quality deterioration due to an increasing anthropogenic pressure. Altogether, these are relevant aspects to consider regarding Ria Formosa present and future management, including climate change and anthropogenic pressures susceptibility assessment and to use them within an international context by comparison with other similar systems. Highlights: Spatial and temporal variability of the water quality of Ria Formosa was assessed. Spatially, the lagoon edges and the estuarine region present the highest nutrients. Land runoff during Wet survey can justify peak nitrate and ammonium concentrations. Diffusion processes from the sediments can explain phosphate maximum during Summer. Temporally, water quality of Ria Formosa has been improved over the last 40 years.